COMPARATIVE STUDY THE IMPACT OF COVID-19-2020 AND THE SPANISH-1920 FLU IN AN INTERNATIONAL POLITICAL ECONOMIC PERSPECTIVE - Warsito , Tulus (Journal of Social Political Sciences, 2020)
The impact of COVID-19’s transmission affects not only the health sector but also almost all sectors of community life, especially economic and social political stability. Until this article was written, this virus has caused more than 650 thousand victims. Resulting in a wave of layoffs of more than 50 million workers. The social panic due to the adoption of the WHO Protocol has created Global Totalitarian, global uniformity, everywhere people are not allowed to leave the house, even if they have to go outside the house they must wear a mask, keep social distancing and always wash their hands with soap. Though COVID-19 is not the first pandemic. A similar pandemic happened a century ago, the Spanish Flu of 1920, although it claimed more casualties, the global impact was not that bad as what COVID-19 does today. This paper wants to explore further about; why does COVID-19 have more worldwide and uniform influence than the Spanish Flu? Why did COVID-19 influence the international poltical economy?